Bureaucratic Reforms for Human Resource Improvement in the Corruption Crime Directorate of the Criminal Investigation Agency of Indonesian National Police (Bareskrim Polri) - Arsyil Mukmin Risalaita Sangadji; Chrysnanda Dwilaksana; Riska Sri Handayani (Transpublika Publisher, 2025)
This research aims to analyze the implementation of bureaucratic reform at the Directorate of Corruption (Dittipidkor) of the Criminal Investigation Agency of Indonesian National Police (Bareskrim Polri) and formulate strategies to improve the quality of human resources (HR) through bureaucratic reform. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results showed that the implementation of bureaucratic reform in Dittipidkor has been carried out by aligning the organizational structure, governance, and HR management by the direction of the Police's bureaucratic reform policy, but there are still aspects that need to be optimized such as simplifying workflows, implementing information systems, and increasing investigator competence. The recommended strategies for improving the quality of human resources include improving the competency-based recruitment system, strengthening education and training, implementing a merit-based promotion system, improving remuneration and welfare, and optimizing supervision and enforcement of the code of ethics. Implementation of these strategies needs to be supported by leadership commitment, effective change management, and synergy with internal and external stakeholders.